Assessing the Physicochemical, Nutritional and Sensory Properties of Cake Made with Wheat and Orange-Fleshed Sweet Potatoes Flour Blend - Sampson, Gilbert Owiah; Abiire, Olivia (Discoveries in Agriculture and Food Sciences, 2025)
This study evaluated the replacement of wheat flour with orange-fleshed sweet potato (OFSP) flour in terms of its proximate composition, functional characteristics, and sensory properties in cakes. Five treatments were made: AA (100% wheat), AB (80:20), AC (70:30), AD (60:40), and AE (50:50 wheat: OFSP). The proximate composition data show that moisture contents ranged from 16.62% (AC) to 21.46% (AD). Crude protein levels slightly increased with substitution from 10.02% (AA) to 12.13% (AC), before decreasing at the higher levels. Crude fat showed a decline with 39.07% in AA and 28.08% in AD. Crude fibre showed a significant improvement, rising from 0.22% in AA to 1.22% in AE. Also, the carbohydrate content in AE was 39.71% in comparison to 28.28% in AA. These results indicate that OFSP improves the nutritional value of cakes by increasing dietary fibre and carbohydrate content. OFSP addition had an impact on functional properties as well. Water absorption capacity (WAC) was 140 g/g for AA and increased with substitution, while oil absorption capacity (OAC) showed its peak value at 146 g/g for AA and showed minimal change with substitution. Bulk density showed a decrease from 0.543 g/cm³ in AA with increasing substitution of OFSP, which indicates lighter flour blends. Functional characteristics were affected by the inclusion of OFSP. Water absorption capacity (WAC) was 140 g/g for AA, and it increased further with the addition of OFSP. Oil absorption capacity (OAC) was highest at 146 g/g for AA. The OAC showed minimal variation afterwards with the inclusion of OFSP. Bulk density was lowest at 0.543 g/cm³ for AA and increased with increasing inclusion of OFSP, showing that the flour mixtures were lighter. For analysed AA, emulsion activity (EA) was 43.88% and foam capacity (FC) was 12.92%, both of which contribute to aeration and aesthetics. Sensory evaluation pertaining to colour, aroma, taste, texture and overall acceptability was conducted by 50 semi-trained panellists using a hedonic scale of 1-9. Based upon the ANOVA, cakes where the AA was substituted at 30% OFSP received acceptability scores similar to the control when the ratings were subsequently analysed. Acceptability was found to be highest for average colour (8.39± 0.92) and taste (8.08± 1.32); however, for cakes with 40%-50% substitution, the ratings for texture and overall likeability were negatively influenced. Statistically significant differences were noted for taste (P=0.034) and texture (P<.001), while colour and aroma differences were not provable as statistically significant. It was concluded that OFSP substitution at rates of 30% or less improved the nutritional quality without a reduction in sensory appeal, consistent with a current trend in health-based product development. This study has shown that OFSP has potential for utilisation in bakery products to improve nutritional quality while also reducing post-harvest waste and, at the same time, supporting local agricultural practices.